Antibacterial Activity of Zanthoxylum acanthopodium DC. Against Streptococcus viridans: An Evaluation of Growth Inhibition Potential - Dohude, Gostry Aldica; Ridho, Muhammad Fathur; Hanafiah, Olivia Avriyanti; Rusdy, Hendry (Journal of Syiah Kuala Dentistry Society, 2024)
Background: The oral cavity serves as the primary entry point for food and harbors various microorganisms, some of which can cause post-tooth extraction infections, such as dry sockets. One of the bacterial species responsible for this condition is S. viridans. Infection prevention is commonly achieved through the administration of antibiotics; however, excessive use of antibiotics can contribute to bacterial resistance. As a result, there is growing interest in exploring natural alternatives for infection control. One potential natural antibacterial agent is Andaliman fruit (Zanthoxylum acanthopodium DC.), which is traditionally recognized for its medicinal properties. Objective: This study aims to evaluate the antibacterial activity of Andaliman fruit extract (Zanthoxylum acanthopodium DC.) against S. viridans in vitro. Methods: This study employed a laboratory experimental approach using Andaliman fruit extract at various concentrations (50%, 25%, 12.5%, 6.25%, and 3.125%). Chlorhexidine digluconate 0.2% was used as a positive control, while Dimethyl sulfoxide (DMSO) was a negative control. The antibacterial activity was assessed by applying these concentrations to paper discs and measuring the inhibition zones formed. Results: Statistical analysis using the Kruskal-Wallis test showed a significant antibacterial effect of Andaliman fruit extract with a p-value of 0.000, indicating a concentration-dependent response in inhibiting S. viridans growth. Conclusion: Andaliman fruit extract exhibits antibacterial activity against S. viridans, with the most effective concentration being 50%. However, its inhibitory effect remains lower than that of the positive control (Chlorhexidine digluconate 0.2%), suggesting that further research is needed to enhance its antibacterial potency.